1999
DOI: 10.1021/ar980015q
|View full text |Cite
|
Sign up to set email alerts
|

From Tars to Products:  How To Disentangle the Reactions of Nitrobenzenes with Nucleophiles

Abstract: Cristina Paradisi received a Laurea degree in industrial chemistry from the University of Padova (1974) and a Ph.D. in chemistry from the University of California at Santa Cruz (1980). Researcher of the Italian National Council of Research (CNR) and, since 1992, Associate Professor in chemistry at the University of Padova. Main research interests: reactivity and mechanisms in solution, gas-phase ion chemistry, and, most recently, decomposition of organic compounds in nonthermal plasmas and the role of ionic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…It has been reported that in the reaction of nitrobenzene derivatives [29,30] and o-nitroanilines [9,28,31] in basic media, azoxybenzene derivatives are formed. Therefore, it is possible that azoxybenzene compounds are formed in our reaction system under N 2 .…”
Section: Kinetic Studies In 60 % 14-dioxane/h 2 Omentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that in the reaction of nitrobenzene derivatives [29,30] and o-nitroanilines [9,28,31] in basic media, azoxybenzene derivatives are formed. Therefore, it is possible that azoxybenzene compounds are formed in our reaction system under N 2 .…”
Section: Kinetic Studies In 60 % 14-dioxane/h 2 Omentioning
confidence: 99%
“…[6,9,28] The reduction of nitro to nitroso groups of benzene derivatives in basic solution is a well-documented reaction that depends on the oxygen content of the reaction media. [29,30] In addition, the yield of 7-nitro-2-propyl-5-(trifluoromethyl)-1H-benzimidazole 3-oxide obtained from N-butyl-2,6-dinitro-4-(trifluoromethyl)aniline increases when the reaction is carried out under N 2 . [8] Thus, we investigated the effect of N 2 on the kinetics and product distribution of the reaction of 3 with NaOH in 60 % 1,4-dioxane/H 2 O.…”
Section: Kinetic Studies In 60 % 14-dioxane/h 2 Omentioning
confidence: 99%
“…1, 4 One recent article has mentioned briefly that 3-chloronitrobenzene reacts with the ethanethiolate anion so as to displace a hydrogen atom, leading to the formation of some thioalkylation products. 1 However, the amount of such products was too small to indicate the preparative potential of this substitution reaction. 5 This would probably be due to the high ability of thiolate anions to act as a reducing agent for the nitro group.…”
Section: Introductionmentioning
confidence: 97%
“…The situation is more complex for systems involving competing reactions, which, under otherwise identical experimental conditions, can give different products depending only on the extent of cationϪanion association. [5] Ion association phenomena thus need to be properly understood and considered in the context of planning new synthetic procedures.…”
Section: Introductionmentioning
confidence: 99%